Automated ambient desorption-ionization platform for surface imaging integrated with a commercial Fourier transform ion cyclotron resonance mass spectrometer - Pól, Jaroslav; Vidová, Veronika; Kruppa, Gary; Kobliha, Václav; Novák, Petr; Lemr, Karel; Kotiaho, Tapio; Kostiainen, Risto; Havlícek, Vladimír; Volný, Michael (Analytical chemistry, 2009)
A fully automated atmospheric pressure ionization platform has been built and coupled with a commercial high-resolution Fourier transform ion cyclotron resonance mass spectrometer (FTICR-MS) instrument. The outstanding performance of this instrument allowed screening on the basis of exact masses in imaging mode. The main novel aspect was in the integration of the atmospheric pressure ionization imaging into the current software for matrix-assisted laser desorption ionization (MALDI) imaging, which allows the user of this commercial dual-source mass spectrometer to perform MALDI-MS and different ambient MS imaging from the same user interface and to utilize the same software tools. Desorption electrospray ionization (DESI) and desorption atmospheric pressure photoionization (DAPPI) were chosen to test the ambient surface imaging capabilities of this new ionization platform. Results of DESI imaging experiments performed on brain tissue sections are in agreement with previous MS imaging reports obtained by DESI imaging, but due to the high resolution and mass accuracy of the FTICR instrument it was possible to resolve several ions at the same nominal mass in the DESI-MS spectra of brain tissue. These isobaric interferences at low resolution are due to the overlap of ions from different lipid classes with different biological relevance. It was demonstrated that with the use of high-resolution MS fast imaging screening of lipids can be achieved without any preseparation steps. DAPPI, which is a relatively new and less developed ambient ionization technique compared to DESI, was used in imaging mode for the first time ever. It showed promise in imaging of phytocompounds from plant leaves, and selective ionization of a sterol lipid was achieved by DAPPI from a brain tissue sample.
Keywords: cyklotrony; systémová integrace; Mass Spectrometry; hmotnostní spektrometrie; molekulární zobrazování; atmosférický tlak; Salvia officinalis; Fourierova analýza; Cyclotrons; Atmospheric Pressure; myši; Plant Leaves; Mice; Fourier Analysis; automatizace; zvířata; Molecular Imaging; Automation; Animals; mozek; Brain; listy rostlin; Surface Properties; Systems Integration; povrchové vlastnosti; šalvěj lékařská